Studi Etnolinguistik: “I Langit Bintang Pitu, I Bumi Kal Pitu Mata” dalam Meningkatkan Jiwa Entreprenuership Masyarakat Adat Gayo - Linge, Abdiansyah (TSAQOFAH, 2023)
Entrepreneurship is part of economic activity closely related to culture or customs that become ideas, knowledge, and behavior. The Gayo community is a group that tightly holds traditional values in life. However, changing times are shifting the role of the Gayo community in entrepreneurial activities, potentially making them spectators in economic changes. Thus, the ideas and knowledge of the Gayo community in entrepreneurship need to be strengthened. One determining variable is the cultural values of the Gayo community itself. This paper attempts to construct cultural values that can encourage the entrepreneurial spirit of the Gayo community using a descriptive-ethnographic approach. One of the constructed values is: "I langit Bintang pitu, I bumi kal pitu mata," which holds spiritual, planning, economic resource sustainability, and moral values. These values can become ideas and knowledge that can change economic behavior, especially in entrepreneurship. These values are built based on ethnolinguistics, rationalized, and internalized to become behavior.